HUBUNGAN KOMUNIKASI PERAWAT TERHADAP TINGKAT KEPUASAN PASIEN DI RS PKU MUHAMMADIYAH YOGYAKARTA - Lilis Awaliyah (PSIK 11 UMY, 2011)
The development of clinical quality and clinical service generally begin from the nurse through from variety of activity, such as; cluster of quality control, applying of nursing standard, problem solving approach, although problem audit. Carried out of nursing care service very extremely depend on employee or human resource aspect as quality although quantity. Nurse resources are the highest quantity health care service in hospital. The purpose of study was to know the correlations between Nur